2012
DOI: 10.1097/ico.0b013e3182254b42
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Chloride Channels in the Lacrimal Glands of a Rabbit Model of Sjögren Syndrome

Abstract: Purpose To test the hypothesis that expression of Na+-K+-2Cl− co-transporter-1 (NKCC1), cystic fibrosis transmembrane conductance regulator (CFTR), and chloride channel 2 γ subunit (ClC2γ) in the lacrimal glands (LG) of rabbits with induced autoimmune dacryoadenitis (IAD) are changed. Methods LGs were obtained from adult female rabbits with IAD, and age-matched female control rabbits. LGs were processed for laser capture microdissection, real time RT-PCR, western blot, and immunofluorescence. Results In ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
2
27
1
Order By: Relevance
“…CFTR activators may be particularly suited for disorders of the lacrimal gland, such as primary Sjögren's syndrome, by stimulating fluid transport across the intact corneal and conjunctival epithelia. CFTR activators probably exert their major prosecretory effect at the ocular surface, although there is indirect evidence for CFTR expression and function in lacrimal gland (43)(44)(45)(46). We cannot rule out direct stimulation of lacrimal (or Harderian) secretion by CFTR activators because of possible limited penetration of topically delivered compound to intraorbital glandular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…CFTR activators may be particularly suited for disorders of the lacrimal gland, such as primary Sjögren's syndrome, by stimulating fluid transport across the intact corneal and conjunctival epithelia. CFTR activators probably exert their major prosecretory effect at the ocular surface, although there is indirect evidence for CFTR expression and function in lacrimal gland (43)(44)(45)(46). We cannot rule out direct stimulation of lacrimal (or Harderian) secretion by CFTR activators because of possible limited penetration of topically delivered compound to intraorbital glandular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…They depend on H 2 O transport proteins (aquaporins [AQPs]) [25][26][27] and ion transport proteins [28][29][30][31][32] arrayed in the cells' apical-and basallateral plasma membranes. The ion transport proteins in the acini include Na þ /H þ exchangers (NHE), 29 Cl À /HCO 3 À exchangers (AE), 30 and Na þ -K þ -2Cl À cotransporters (NKCC1) 31 which function in the basal-lateral plasma membranes, Cl À selective channels (ClC3 and CFTR) 32,33 -which function in the apical membranes, 34 and Na þ /K þ exchange pumps (Na,KATPase), which some evidence indicates function in both the apical-and the basal-lateral membranes. 28 The mechanism in the acini secretes Cl À ions into the lumens, thereby generating a negative transepithelial voltage difference; the voltage difference presumably drives Na þ ions into the lumens via the zonulae occludens and zonulae adherens that link adjacent epithelial cells, 35 and the osmotic imbalance that results from the net secretion of Cl À and Na þ draws H 2 O through the epithelium.…”
mentioning
confidence: 99%
“…More detailed understanding of LG function is therefore essential in order to develop novel approaches in the treatment of dry eye disease (9). Unfortunately, duct cells have been understudied for many years as compared to acinar cells, although recent advances clearly indicated that these duct cells play critical and indispensable roles in LG production (12,13,15,(37)(38)(39). Our laboratory is focusing on the clarification of the role of…”
Section: Discussionmentioning
confidence: 99%